The Correlation Between Knowledge Levels Regarding Gestational Hypertension and Its Prevalence: A Cross-Sectional Study Among Pregnant Women - Lisnawati Lisnawati; Sarliana Sarliana; Henrietta Imelda Tondong; Sri Yanti Kusika; Niluh Nita Silfia; Ilma Cahya Putri; Nasrul Nasrul; Zainul Zainul; Anna Veronica Pont; Taqwin Taqwin (Journal of Health and Nutrition Research, 2026)
Hypertension during pregnancy is one of the most serious complications that can increase the risk of morbidity and mortality for the mother and fetus. Pregnant women's understanding of hypertension during gestation plays a very important role in the prevention and management of these conditions. This study aims to analyze the relationship between pregnant women's knowledge of gestational hypertension and the prevalence of hypertension in the Talise Health Center's work area in Palu City, Central Sulawesi. This study used an analytical cross-sectional design with 51 respondents selected through convenience sampling. Data were obtained through a structured questionnaire to assess knowledge levels and through blood pressure checks to detect hypertension. Data analysis was performed using the chi-square test. The study found that the majority of respondents' knowledge fell into the poor (37.3%), sufficient (33.3%), and good (29.4%) categories. The prevalence of hypertension among respondents was 56.9%. Statistical tests showed that there was a significant relationship between knowledge about gestational hypertension and the prevalence of hypertension (p=0.007). These findings suggest that improving maternal knowledge through health education may help reduce the risk of hypertension during pregnancy. However, the cross-sectional design of this study limits the ability to establish causal relationships